Challenges and solutions in reinforcing self-built homes: experiences from Villa Maria del Triunfo, Lima, Peru - Medrano‐Sánchez, Emilio J.; Fabian, Magaly C. (Frontiers in Built Environment, 2025)
This study assesses H-shaped steel profiles (W8×31) as a retrofit solution for self-built dwellings in the Human Settlement (AA.HH). Ciudad de Gosen, Villa María del Triunfo (Lima, Peru). A four-part workflow was applied: i. field diagnosis with the Peruvian National Institute of Civil Defense (INDECI, by its Spanish acronym) checklist to classify seismic vulnerability and document construction pathologies; ii. numerical modeling in “Extended Three-Dimensional Analysis of Building Systems” (ETABS) v18 under Peruvian Standard E.030 to characterize story drift, torsion, and center of rigidity; iii. retrofit design that anchors and welds W8×31 profiles along critical load paths; and iv. experimental verification at National University of Engineering (UNI) Materials Testing Laboratory (LEM) following Peruvian Technical Standard (NTP) 350.405:2019 on representative columns and beams. Retrofitted specimens reached the testing machine’s maximum axial load of 686 kN (70,000 kgf) with only minor cracking between 245 and 324 kN (25,000–33,000 kgf), confirming concrete-steel compatibility and increases in stiffness and axial capacity. Given the limited number of numerical models and laboratory specimens, the findings were integrated in a descriptive way to show the consistency between the ETABS simulations and the composite behavior observed in the tests. These results position W8×31 profiles as a feasible, constructible option for seismic risk reduction in self-built contexts and provide a technical bridge toward guidelines, on-site protocols, and community training aligned with the Sustainable Development Goal (SDG) for safe, resilient, and inclusive housing.